Manning, Scott County - Davis, Macy (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a paper about Manning, Kansas. Manning is located in Keystone Township in Scott County, Kansas. It existed from 1887 to 1955. The Manning Jayhawkers 4-H Club served as a factor of persistence in Manning. It now serves as Manning’s primary legacy. This study provides the story of Manning and the Manning Jayhawkers through maps, historic and modern photographs, town histories, 4-H records, field work, and interviews.
Macy Davis, “Manning, Scott County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/194.
Keywords: Missouri Pacific Railroad; Scott City; Scott County Fair; Scott County; Manning; Charlie Conine